Common capacity for far-red light photosynthesis in a canyon thermophilic freshwater system - Ivan J. Moreno; Alexander Bogdanov; Brian Palenik (Extremophiles, 2026)
Photosynthetic life is based on absorbing sunlight and turning it into biologically usable energy. In many cases however, canopy-like structures and cavern-like habitats in terrestrial environments can limit the intensity and alter the spectra of light. One acclimation to use filtered light in the near infrared range, typically between 700 and 800 nm is named far-red light photoacclimation or FaRLiP as in recent studies of cyanobacteria. Here we report the common capacity for FaRLiP in the dominant cyanobacterial genera in a canyon hot spring microbial mat ecosystem. We identified FaRLiP in the genomes of cyanobacterial isolates and the metagenomes of mat samples. We show using absorption spectroscopy and HPLC that under far red-light specific isolates show an increase in far red-light absorption and the presence of Chl f . Springs in narrow canyons are a microniche where FaRLiP seems highly ecologically advantageous.